Predicting Academic Motivation based on School Climate, Mediated by Metacognitive Reading Strategies in Students with Learning Disabilities - Ebrahimi , Bita; Kadivar , Parvin; Kamkari , Kambiz (Applied Family Therapy Journal (AFTJ), 2020)
Aim: This study was conducted to predict academic motivation based on school climate, mediated by metacognitive reading strategies. Method: This was a descriptive-correlational study conducted by structural equation modeling (SEM). The statistical population included all students with learning disabilities in the first grade of high school in Tehran in the academic year of 2019-2020. The sample size was 300. The sampling method was multi-stage clustering in the first stage and purposive in the second stage. The study tools included the Colorado Learning Disability Questionnaire (Wilcott et al., 2011), the Harter Academic Motivation Questionnaire (1981), the Ojaghi School Atmosphere Questionnaire (1998), and the Metacognitive Awareness of Reading Strategies Inventory (MARSI) (2002). Results: According to the results, the model fit indices are in good condition. School climate has a significant direct effect on the academic motivation of students with learning disabilities (p